Antimicrobial Activity of Bacteriocin Produced by Weissella cibaria NRIC0136 - Hashium, Abdulkareem Jasim; Hamza, Subhi Jawad; Aldujaili, Nawfal Hussein (Al-Kufa University Journal for Biology, 2010)
A total of 1070 isolates of lactic acid bacteria were obtained from 50 samples of different sources (fermented foods 30 samples, chicken intestine (10 samples) and human intestine and vagina (10 samples). Three hundred isolates were isolated from Baghdad, Iraq(220 isolates from human intestine and vagina and 80 isolates from fermented foods) and the others from Bangkok(Thailand). These isolates were screened for bacteriocin production using the agar well diffusion method and Shigella dysenteriae DMST 15110 was used as an indicator strain. Seventy two isolates gave clear inhibition zones against growth of indicator strain. One isolate , F14 (from Thailand fermented fish) that produced largest inhibition zone against the indicator strain was chosen for further study, and identified as a Weissella cibaria NRIC0136 by morphological, physiological properties and PCR amplification, sequencing and comparison of 16S rRNA gene. The neutralized cell free supernatant of W. cibaria NRIC0136 inhibited growth of a number of standard strains of pathogenic microorganisms including Listeria monocytogenes DMST 17303, Enterococcus faecalis ATCC 29212, Salmonella sp DMST 22842 and Shigella dysenteriae DMST 15110. The optical density at 660nm (2.253) and inhibition zone (18 mm) against the indicator strain, Shigella dysenteriae DMST 15110 were maximum when growth temperature employed was30°C.